1956
DOI: 10.1063/1.1700809
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of Gaseous and Crystalline Cyanogen Halides

Abstract: The infrared spectra of gaseous ClCN and BrCN at room temperature are reported for the LiF, NaCl, KBr, and CsBr prism regions. Several upper stage bands as well as bands due to C13 appear in both spectra. Assignments are given, from which a number of the vibrational constants are evaluated and the Fermi resonant levels treated by a first-order perturbation method. The spectra of crystalline ClCN, BrCN, and ICN at −180°C is also recorded. Absorption bands, including several due to C13 and N15, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1964
1964
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…8 Sample dimensions, spectroscopic equipment and techniques and calibration procedures were essentially the same as those described in a previous paper, 1 and details will not be repeated here. 6,7 Wavenumber accuracy for the present work is estimated to be š1 cm 1 , and pressure accuracy is about 0Ð1 GPa for values up to 8 GPa and 0Ð2 GPa at higher values, where there is some evidence of gradients in the samples, as indicated by the widths of the ruby fluorescence lines. 3, where the points have been fitted to quadratic curves as a guide to the eye.…”
Section: Methodsmentioning
confidence: 51%
See 1 more Smart Citation
“…8 Sample dimensions, spectroscopic equipment and techniques and calibration procedures were essentially the same as those described in a previous paper, 1 and details will not be repeated here. 6,7 Wavenumber accuracy for the present work is estimated to be š1 cm 1 , and pressure accuracy is about 0Ð1 GPa for values up to 8 GPa and 0Ð2 GPa at higher values, where there is some evidence of gradients in the samples, as indicated by the widths of the ruby fluorescence lines. 3, where the points have been fitted to quadratic curves as a guide to the eye.…”
Section: Methodsmentioning
confidence: 51%
“…4 It indicates that the two stretching modes, 1 (C-N) and 2 (C-Br), each produce two components in the crystal, as a result of coupling of the two molecules in the unit cell, one being Raman-and the other infrared-active. 6,7 As far as we are aware, no previous spectroscopic studies of solid BrCN at high pressures have been reported. There are also three Raman-active optical translational modes.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational polyad 1 /2 2 has been investigated in the infrared with low resolution (8). This polyad, which is of medium intensity, forms a doublet, with centers at 571 and 691 cm Ϫ1 .…”
Section: Introductionmentioning
confidence: 99%
“…The ether-extracted portion was distilled to give 1.10 g (82%) of ZV-methyl-ZVethylaniline. Diethylcyanamide was analyzed as follows: ir (thin film) 2213 cm-1 (strong, CN); nmr (CCI3) 1.25 (t, CH$, 6 H) and 3.20 (q, CH2, 4 H); mass spectrum m/e (rel abundance) 98 (M+, 34), 87 (6), 85 (42), 84 (6), 83 (6), 70 (11), 69 (12), 58 (25), 56 (6) , 55 (100), 53 (6), 49 (9), 48 (10), 47 (22), 44 (9), 43 (98), 42 (20), 41 (6).…”
mentioning
confidence: 99%
“…The nmr spectrum (CC14) had signals at 0.91 (t, CH3, 3 ), 1.07-1.80 (br, CH2, 4 H), 2.85 (s, CH3, 3 ), 3.17 (t, CH2, 2 H), 6.43-6.63 (m, phenyl ring, 3 ), 6.91-7.23 (m, phenyl ring, 2 H). Di-n-butylcyanamide was characterized as follows: bp 70-71°( 0.5 mm); ir (thin film) 2205 cm-1 (strong, CN); nmr (CC14) 0.97 (t, CH3, 6 ), 1.20-1.90 (m, CH2, 8 H), 2.97 (t, CH2, 4 H); mass spectrum m/e (rel abundance) 154 (M+, 23), 139 (7) , 125 (9), 112 (10), 111 (44), 98 (9), 97 (7), 86 (8), 83 (7), 70 (11), 69 (100), 57 (44), 55 (19), 43 (13), 42 (10), 41 (41), 39 (8).…”
mentioning
confidence: 99%